THE EFFECTIVENESS OF THE TEAMS GAMES TOURNAMENT (TGT) MODEL IN IMPROVING ENGLISH VOCABULARY MASTERY (ELang | An English Language Education Journal, 2023)
This research paper is entitled “The Effectiveness of The Teams Games Tournament (TGT) Model in Improving English Vocabulary Mastery (A Quasi-experimental study done in the seventh grade students of Junior High School)”. The aims of the research is to know whether or not there is significant difference in the students’ scores before and after the treatment by using TGT learning model for improving student’s English vocabulary mastery and to find out the students’ responses through the use of TGT learning model in improving their vocabulary mastery. The population of this research is the seventh grade students of Margahayu 1 junior high school which consists of ten classes from seventh grade. The writer take 32 students as the sample of the study. In this study there are two groups, the experimental group and the control group. The sample of this research are class VII-A as experimental group and VII-B as control group. In obtaining the data, the writer uses pre-test, post-test and questionnaires. From the computation of pre-test and post-test scores result shows that with the degree of freedom (df)= N1 + N2 – 2 = 32 + 32 - 2 = 62, at P = 0,5 of two tailed, the critical value of t is 1.998. The result of pretest is 0.8125 lower than the critical value of t (t-table) 1.998 (0.8125 < 1.998). It means that there is no significant difference between in english vocabulary mastery between theexperimental group and the control group before treatment. After the experimental group was given the treatment, the t-observed value is 4.106. So t-observed was higher than of t-tbale (4.106 > 1.998). It means that there was significant difference between TGT learning model and the conventional method in improving English vocabulary mastery to seventh grade of Margahayu 1 junior high school. It also supported by the students’ response in questionnaires. The result showed 32 students (78% of the students) agreed that TGT learning model helped them to understand meaning and increase vocabulary, to remember new vocabulary, to help each other in the learning process, and TGT learning model helped them in improving English vocabulary mastery. This means that the students’ responses about TGT learning model are positive